AUTOIMMUNE CYTOPENIAS IN CHRONIC LYMPHOCYTIC LEUKEMIA, FACTS AND MYTHS - Pavankumar Tandra; Jairam Krishnamurthy; Vijaya Bhatt; Kam Newman; James O Armitage; Mojtaba Akhtari (Mediterranean Journal of Hematology and Infectious Diseases)
CLL has been defined as presence of more than 5000 small mature appearing monoclonal B lymphocytes with a specific immunophenotype in peripheral blood. It is a well-known fact that CLL is associated with autoimmune cytopenias. CLL cells are CD5+ B lymphocytes, and usually are not the “guilty” cells which produce autoantibodies. T cell defect is another characteristic of CLL and the total number of T cells is increased, and there is inversion of the CD4/CD8 ratio. Autoimmune hemolytic anemia (AIHA) is the most common autoimmune complication of CLL and has been reported in 10-25% of CLL patients. However, the stage-adjusted estimated rate of AIHA in CLL is about 5%. Conversely, CLL is three times more common in patients who present with AIHA. Direct agglutinin test (DAT) is positive in 7-14% of CLL patients but AIHA may also occur in DAT negative patients. Autoimmune thrombocytopenia (AIT) is the second most common complication of CLL and has been reported in 2-3% of patients. DAT is positive in AIT but presence of antiplatelet antibodies is neither diagnostic nor reliable. Autoimmune neutropenia (AIN) and pure red cell aplasia (PRCA) are very rare complications of CLL and like other autoimmune complications of CLL may occur at any clinical stage. It is believed that most case reports of AIN and PRCA in CLL actually belong to large granular lymphocytic leukemia (LGL). Non-hematologic autoimmune complications of CLL including cold agglutinin disease (CAD), paraneoplastic pemphigus (PNP), acquired angioedema, and anti-myelin associated globulin are rare. Before starting any treatment, clinicians should distinguish between autoimmune cytopenias and massive bone marrow infiltration since autoimmune complications of CLL are not necessarily equal to advanced disease with poor prognosis. According to IWCLL guideline, steroids are the mainstay of treatment of simple autoimmunity. Intravenous immunoglobulin (IVIg), cyclosporine, and rituximab are used in complex, steroid refractory cases. Monotherapy with purine analogues and alkylating agents should be avoided as they may increase CLL associated autoimmune complications